Optimization of fresh agricultural product supply chains in Shandong Province under the cloud logistics model - Xing, Yongliang; Zainol, Zuraidah (International Journal of Accounting, Finance and Business, 2025)
Shandong Province holds a pivotal position as a key region for the production and supply of fresh agricultural products. However, fresh agricultural products, due to their perishability and difficulty in long-term storage, impose higher and more stringent requirements on the logistics system compared to general agricultural products. Currently, the fresh agricultural product supply chain in Shandong is relatively backward, characterized by low levels of informatization and an immature cold-chain transportation system. This results in inefficient logistics operations, high costs and losses, difficulties in ensuring product quality, and concerns over safety risks. To address these challenges, this study constructs an optimization model for the fresh agricultural product supply chain in Shandong based on the cloud logistics model. The empirical results indicate that the cloud logistics–based optimization model significantly enhances logistics coordination efficiency, reduces average transportation time, lowers spoilage and loss rates, and improves cost-effectiveness across the supply chain. The model also strengthens data sharing and real-time monitoring, which contribute to higher product quality stability and supply reliability. Based on these findings, this study recommends several policy measures, including: accelerating the digital transformation of the agricultural logistics sector; increasing investment in cold-chain infrastructure; establishing a unified provincial cloud logistics information platform; encouraging collaboration among producers, logistics firms, and retailers; and implementing supportive financial and regulatory policies to promote technology adoption. The model aims to enhance the circulation efficiency of fresh agricultural products, reduce operational costs, and thereby increase socio-economic benefits.